Adolescent attitudes towards tanning: does age matter? - Dennis, Leslie K. (2009)
Adolescents seem to be obsessed with tanning. One third of both adolescents and adults report sunbathing. On average, about 20% of adolescents report ever-using of artificial UV tanning devices with 15% currently using them. Tanning attitudes appear similar for adolescents and adults. The top three reasons for tanning included beliefs that a tan makes them more comfortable socializing with friends, looks better and is attractive. The top reason for using artificial UV tanning devices is also aesthetics, followed by relaxation. Other reasons for using artificial UV tanning devices include vacation preparation and to gain a protective base. Attitudes related to appearance that result in more frequent tanning may be difficult to change.